A study on elevation of troponin I in ischemic stroke as an independent prognostic marker of outcomes - Thapa, Pradeep; Agrawal, Jagdish Prasad; Baniya, Rajani (Nepal Journal of Neuroscience, 2020)
Background: Stroke is the second leading cause of death worldwide, comprising approximately 10% of all deaths. A substantial number of stroke patients have elevated cardiac troponin levels and are associated with poorer prognosis.Methods: This was a prospective observational study conducted for 1 year at Tribhuvan University Teaching Hospital, in which 101 acute ischemic stroke patients were enrolled. Data included vital signs, laboratory parameters, and clinical features evaluated at the time of admission. The National Institute of Health Stroke Scale (NIHSS) and modified Rankin scale (mRS) were used to assess stroke severity and outcomes.Results: Elevated troponin I (> 0.034 ng/mL) was observed in eight (7.9%) patients. Compared to patients with normal troponin I, patients with elevated troponin I were older(mean age 61vs 59.68 years), had higher blood glucose( 10.6 vs. 7.04 mmol/L), higher median white blood cells( 9.3 vs. 8.9 1,000/m3) and creatinine levels(119.5 μmol/L vs. 95.9 μmol/L), higher mean NIHSS scores on admission(16 vs. 8.6), and discharge(14.5 vs. 6.8), higher median mRS scores( 4.13 vs. 1.8) at discharge(p